THU0153 Open-label evaluation of the quality of life of patients treated with etanercept in common rheumatology usage (ecru). (1st June 2001) - Hermann, J; Aytekin, A; Bröll, J; Dunky, A; Nowak, J; Singer, F; Smolen, J
Abstract : Background: Tumour Necrosis Factor-alpha (TNFα) plays an important role in the inflammatory processes of RA and the resulting joint pathology. Etanercept is a dimeric fusion protein consisting of two p75 TNFα receptors linked to the Fc portion of the human IgG1. This protein can bind and inactivate up to two free molecules of TNFα. The safety and efficacy of etanercept has been demonstrated in human clinical trials of early RA and active RA. Objectives: This current study was designed to further evaluate safety and efficacy of etanercept. One of the objectives was also to evaluate quality of life of patients treated with this substance by means of SF-36. Methods: This study was conducted in 55 Austrian outpatients with active RA who have failed at least one disease-modifying anti-rheumatic drug (DMARD). Each patient received twice-weekly subcutaneous injections of etanercept 25 mg administered over a treatment period of 16 weeks. Stable doses of methotrexate (MTX) and steroids were permitted. For SF-36 interpretation the normal rages of the most recent published Canadian data and SF-36 Manual were used. Results: At baseline, all 8 domains revealed substantially lower score than observed in healthy subjects. Five of them indicated level of disability of 50% or more. At week 16, all domains improved. Observed improvements ranged from 15 (general health perceptions) to 42, 1 points (role function limited by physical problems). All were clinically significant (more than 5 points improvement). Two domains reached almost level characteristic for a healthy population: social functioning (97% of normal) and mental health (92% of normal). Conclusion: In general, study patients at baseline demonstrated poor functioning in all domains of SF-36 QoL assessment; in five domains their functioning was at least 50% worse than in healthy subjects. The study was conducted in a heavily pretreated population. In spite of that, substantial improvement in the course of the study was observed. Improvement in all domains could be observed already after one week of treatment. At week 16, substantial improvement in all 8 domains was recorded, in two of them reaching almost normal ranges. The significant improvement in Physical Function and Bodily Pain also suggest that work-difficulty may be delayed or prevented in patients treated with etanercept.